RESPON ASIA TENGGARA TERHADAP KEBIJAKAN ANTI TERORISME AMERIKA SERIKAT - , Ezza Hanindya Mufti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study, based on the study of literature on Southeast Asian responses to changes in Southeast Asian anti-terrorism policy has two main objectives. First, to determine what effect anti-terrorism policy of the United States to Southeast Asia after 9/11 and the second goal how Southeast Asia respond to the policy change. This study uses descriptive secondary data collection. The results showed that the changes of anti-terrorism policy of the United States, the issue of global security has quickly spread around the world. The fight against terrorism in Southeast Asia has led to changes in the attitude of the government in dealing with separatism in Southeast Asia. With the help of allies and the use of its power as a superpower state, the United States pressuring countries of Southeast Asia to obey the anti-terrorism policy. This is also done for the United States actually has economic and political interests to the South-East Asia. In general, governments of Southeast Asia increasingly tighten oversight of a number of groups who allegedly have links with Al-Qaeda cooperation such as JI and the MILF. Changes in the government's attitude is also because the role of the United States in implementing global strategy against terrorism. However, anti-terrorism policy of the United States of America shows a failure in view of the fact that the issue of conflict based on religion, conflict, ethnic secession and other fundamentalist conflicts already exist in Southeast Asia long before the 9/11.